Analisis Strata Norma Strata Norma Roman Ingarden Pada Puisi Ibu Pertiwi dan Royan Reformasi Karya Hasan Aspahani - Dian, Dian; Hefni, Asnan; Setyawati, Meita (Adjektiva: Educational Languages and Literature Studies, 2020)
The purpose of this study is to describe the sound layer, the meaning layer, the object world layer, the world layer, and the metaphysical layer in the poem “Mother Pertiwi and Royan Reformasi” by Hasan Aspahani. The data collection technique used in this research is library technique. The result of the research from poetry data using Roman Ingarden strata norm analysis obtained layer of sound, namely mixed rhymes with continuous and broken rhymes and the sound of kakofoni. The layer of meaning obtained are the layer of the world of objects are obtained, namely the main character “nature” and the background of the feeling of sadness, chaos and sadness. The layer of the world, namely the author describe the sadness and state of nature due to the actions of irresponsible humans, so that humans can realize that they can use and protect nature simultaneously. It is found that metaphysical layer of the poet wants to convey how suffering nature is due to irresponsible human hands, arid forests land that is no longer fertile, barren mountains, and damaged oceans, this can result in nature disasters.